2019
DOI: 10.1039/c8cp06975a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the ion-exchange properties of Zn(ii)-incorporated MOR zeolites for the capture of multivalent cations

Abstract: The ion exchange property of MOR zeolites for multivalent cations is improved in the presence of Zn(ii).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Various layer-structured compounds have been applied to remove hazardous ions by exchanging interlayer ions owing to their adjustable distances and substitutable ions in the interlayer spaces. Previous studies indicate that anionic frameworks with highly negative-charged results in strengthening the electrostatic affinity for exchanged cations with highly positive charge. , FJSM-CA contains the anionic layers with highly negative charge, high free void volume percentage (∼37.6% after excluding H 3 O + and lattice H 2 O molecules, calculated by PLATON), numerous uncoordinated O atoms from carboxyl groups of a network, and holds the high water stability, wide pH durability, and excellent radiation resistance (Figures S7, S9, and S12). These advantages provide the possibility of FJSM-CA for the capture of hazardous metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Various layer-structured compounds have been applied to remove hazardous ions by exchanging interlayer ions owing to their adjustable distances and substitutable ions in the interlayer spaces. Previous studies indicate that anionic frameworks with highly negative-charged results in strengthening the electrostatic affinity for exchanged cations with highly positive charge. , FJSM-CA contains the anionic layers with highly negative charge, high free void volume percentage (∼37.6% after excluding H 3 O + and lattice H 2 O molecules, calculated by PLATON), numerous uncoordinated O atoms from carboxyl groups of a network, and holds the high water stability, wide pH durability, and excellent radiation resistance (Figures S7, S9, and S12). These advantages provide the possibility of FJSM-CA for the capture of hazardous metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to emphasize that all the synthesized hydroxyapatite samples exhibited the typical crystalline structure, showing well-defined peak characteristics with high intensity, which correspond to alkalineearth hydroxyapatite structures as was described above; according to these results, it is suggested that there is not a notable structural difference between the Ba-HAp, Sr-HAp, and Ca-HAp samples; however, comparing their nanocrystallinity, it is observed that Ca-HAp is more nanocrystalline than the Ba-HAp and Sr-HAp samples, since the main Ca-HAp peaks are wider and their determined crystallite sizes are smaller. These features can improve the immobilization of Co 2+ ions in their structure, for it is widely known that the physicochemical properties of nanocrystalline materials significantly influence ion-exchange capacity [33]. It is well-known that the sintering temperature needed to obtain materials could change the crystallinity or purity of materials; indeed, the crystalline phases can increase or decrease as a function of temperature [34].…”
Section: Characterization and Co 2+ Ions Adsorptionmentioning
confidence: 99%
“…Another important property of zeolites is ion-exchange. [135,136] In zeolite framework, the negative charge on alumina tetrahedra is compensated by exchangeable cations resulting in an electrically neutral framework. The exchangeable cations, generally from the group I or II ions, can be exchanged with other cations through a solution-based conventional ion-exchange process.…”
Section: Ion-exchange Capacitymentioning
confidence: 99%